2007
DOI: 10.1080/00207450600592107
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Teething and Handedness

Abstract: The aim of this study was to evaluate the role of tooth eruption sequences as an indicator of handedness. The investigation was carried out on 92 healthy children. The questionnaire form was filled out for each child. The form consisted of two parts. In the first part there were questions to determine the demographic features of the children. The second part consisted of the questions to clarify the eruption time and sequence of first primary teeth. Hand preference was evaluated by placing colored pencils dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
1
5
0
2
Order By: Relevance
“…Results on the relationship between laterality and dental eruption are essentially the same to those of similar studies ( 6 , 7 ). In those, even if the evaluation of dentition was not as exhaustive, it was observed that dental eruption might be a good indicator of a child laterality.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Results on the relationship between laterality and dental eruption are essentially the same to those of similar studies ( 6 , 7 ). In those, even if the evaluation of dentition was not as exhaustive, it was observed that dental eruption might be a good indicator of a child laterality.…”
Section: Discussionsupporting
confidence: 83%
“…In other studies previously made on this topic, one limitation lies in the value for the dental eruption order variable that was collected by indirect way (parent questioning), so the data were based on memories, photographs, registrations and recordings, providing not completely reliable information ( 6 , 7 ). Another difference lies in the fact that hand laterality in those studies was evaluated in 3 to 5 years children, but that period could be precocious or premature as it has been considered that in these age span would not yet set a complete maturity in that domain ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hand preference was stated as one of the most important parameters affecting cognitive abilities and proficiency [23,24]. One study of 106 subjects reported that more lesions were found on the left side of righthanded subjects, but the difference was not statistically significant.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%